Knowledge and practices of nurses regarding prevention of hepatitis B and C viral infection: findings from a single center cross-sectional study in Bangladesh - Parvin, Rahima; Jabbar, Md. Abdul; Sultana, Hafiza; Rahman, Mohammad Meshbahur; Rimu, Most Rownak Zahan; Choudhury, Rafaat (Intelektual Pustaka Media Utama, 2025)
The study aimed to evaluate the nurses’ levels of knowledge and practices in preventing hepatitis B and C viral infections in tertiary level hospitals. A cross-sectional study was conducted among 119 nurses in tertiary level hospital by simple random sampling technique. Data were collected by face to-face interview with semi-structured questionnaire and analysis involved the frequency distribution tables, bar diagrams, and proportion (z-tests). The analysis revealed that most of the nurses fell within the 25-34 age groups, and predominantly held a diploma in nursing. Analysis indicated that 95.79% demonstrated good knowledge, whereas 70.59% exposed good practices. Proportion tests revealed significant associations between demographic factors and knowledge/practice levels. Higher educated nurses (poor knowledge, good knowledge: 13.0%, 87.0%; p = 0.021) and those in older age groups (poor practice, good practice: 36.8%, 63.2%; p = 0.002) displayed significantly better knowledge and practices. This study highlights good knowledge among nurses concerning the prevention of hepatitis B and C infections; significant variation exists in the application of preventive practices. Training programs are recommended to bridge the gap between knowledge and practice.